If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23y + 12x + 3 = 0 Reorder the terms: 3 + 12x + 23y = 0 Solving 3 + 12x + 23y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 12x + -3 + 23y = 0 + -3 Reorder the terms: 3 + -3 + 12x + 23y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 12x + 23y = 0 + -3 12x + 23y = 0 + -3 Combine like terms: 0 + -3 = -3 12x + 23y = -3 Add '-23y' to each side of the equation. 12x + 23y + -23y = -3 + -23y Combine like terms: 23y + -23y = 0 12x + 0 = -3 + -23y 12x = -3 + -23y Divide each side by '12'. x = -0.25 + -1.916666667y Simplifying x = -0.25 + -1.916666667y
| 132-6x=4x+12 | | 5-x=-3 | | 8x^2+24x=-4x^2+15 | | x^2+18x+29=0 | | 10+8x=38+x | | x^2+27=0 | | 5x^3+10x^2+5x+10=0 | | 4x+28=14x-92 | | -6x-3x+2=-5x+9x+1 | | 6x+3=2x-7 | | 134=6x+2(4x-17) | | 4(2)+3=15-2(2) | | x^2+14=10x | | 4a+3=15-2a | | 4x+2x-3=-6x+5+x | | 45+5y=180 | | 7k-8+(k+12)=52 | | y=6x+30x^2 | | y=30x^2+6x+0 | | 7-9x=43-16x | | (-3x+4)4=22 | | y=60x^2+7x+0 | | y=60x+7x+0 | | 3(8-x)=27 | | 3k+7k+5k^2= | | 115-4x=3x+10 | | 9x-3-12x=6 | | 86-4x=10x+16 | | 0.25(x-4)=1 | | 3x+8-5x=0 | | 6x^2+4x=-11 | | 3+11x=83+x |